Social Disparities and Food Environment Determinants of Food Insecurity Among Graduate Students in the United States During the COVID-19 Pandemic. (7th June 2021) - Boncyk, Morgan; Froese, Savannah; Ambikapathi, Ramya; Verissimo, Cristiana; Matangi, Evidence; Ruiz, Yumary; Fletcher, CheKenna; AboAlsafa, Dalia; Heniff, Lauren; Gunaratna, Nilupa
Abstract: Objectives: The COVID-19 pandemic is worsening food insecurity and exacerbating social disparities. This study investigated the pandemic's impact on food insecurity, disparities, and determinants among graduate students at Purdue University, a public research university. Methods: Purdue University graduate students completed a Graduate Student Experience in the Research University Survey (gradSERU) in Apr-Jun 2019 and the Fostering Food Security, Health, and Resilience in Graduate Education (FORGE) survey in Nov-Dec 2020, which assessed students' food security, mental and physical health, and academic performance. A validated two-question tool measured food insecurity based on worry over or experience of running out of food without the ability to purchase more. Analyses using logistic regressions were performed in StataSE16. Results: Food insecurity among graduate students doubled from spring 2019 (17%) to fall 2020 (36%, P < 0.001), increasing for all races, genders. Odds of food insecurity in 2020 were higher among students who were African American (OR: 5.7, 95% CI 3.2–10.1), Asian (OR 3.1 [2.1–4.8]), Hispanic or Latino (OR 3.0 [1.8–4.0]), international (OR 1.5 [1.2–1.8]), LGBTQ+ (OR 1.9 [1.4–2.6]), caregiving for adults (OR 2.7 [1.9–3.6]), or funded through fellowships or assistantships (vs. personally funded, OR 1.5 [1.1–2.0]). Food insecure students faced greater stress (OR 3.5 [3.0–4.2]) and reduced ability (OR 0.6 [0.5–0.8]) to attain a healthy diet, with reduced access to stores with fruits and vegetables (OR 0.7 [0.6–0.9]) or considered good quality (OR 0.4 [0.3–0.5]). Food insecure students were more likely (OR 6.7 [5.2–8.6]) or vegetables (OR 8.1 [6.1–10.9]) due to cost. Lack of time (52%), culturally desired foods (11%), and transportation (10%) were limitations to a healthy diet. Conclusions: Graduate student food insecurity increased significantly during the COVID-19 pandemic, particularly among international, minority, and LGBTQ + students, and coincided with lower likelihood of purchasing nutritious foods. Universities should implement policies and services to address persistent and increasing food insecurity and disparities among graduate students. Funding Sources: Protect Purdue Innovations Faculty Grant.